Estudo de viabilidade técnica para implantação semafórica no município de Campo Mourão-Pr - Beyer, Maicon Andrius (2016)
With the growth of cities and the increase of the vehicle fleet occurring exponentially, it becomes apparent the importance of policies to road planning that meet the needs of the population. This work has focused on improving the flow and safety at the intersection located in Campo Mourão, between avenues President John Kennedy, Guilherme de Paula Xavier, the highway Bento Fernandes Dias and Miguel Luiz Pereira street , noting the possibility of traffic signal implementation . The analysis was based mainly Brazilian Manual of Traffic Signs Volume V - traffic lights, and complementary legislation CONTRAN and DENATRAN. The methodology followed the provisions of the aforementioned manual. After the analysis, positive results were presented to semaphore implementation and the need to change in the current configuration, lastly proposed a new configuration to the cross.